Pilot study on cardiac and metabolic responses to moderate-altitude endurance training in middle-distance runners - Polizzi, G.; Giaccone, M.; Gervasi, M.; D'Amato, A.; Palma, A.; Bartolucci, C.; Brandoni, G.; Federici, A.; Lucertini, F. (Medicina dello Sport, 2014)
SUMMARY Aim. Moderate-altitude (2000 m) training can increase endurance performance at sea level; it improves physiological parameters, including maximum oxygen uptake, muscle oxygen extraction, red blood cell volume, plasma hemoglobin mass and concentration, and maximal cardiac output and systolic stroke volume; and it can also reduce resting and submaximal exercise intensity heart rate. To date, no studies have investigated the effects of moderate-altitude training on resting cardiac output and systolic blood pressure, and on the metabolic thresholds commonly used in evaluating endurance athletes. The aim of this study was to evaluate blood, cardiac, and metabolic parameters following training and sojourn at moderate altitude (2000 m above sea level).